PENGARUH GREEN PRODUCT KNOWLEDGE TERHADAP PURCHASE INTENTION MELALUI GREEN TRUST DAN GREEN ATITTUDE - Ardiansyah (Jurnal Ekonomi STIEP, 2023)
The aim of this research is to test the influence of green product knowledge on purchase intention with green trust and green attitude as mediating variables. This research is explanatory research which aims to test and explain the causal relationship between research variables through hypothesis testing. The approach taken in this research is a quantitative research approach. The data used is primary data. The purposive sampling method was used as a sample determination technique. The process of obtaining data is carried out by means of a survey in the form of a questionnaire. In this study, researchers used 100 respondents who were consumers of LED lights. This research uses Structural Equation Modeling (SEM) to test the hypothesis. The findings of this research are as follows. Green product knowledge, green trust and green attitude have a positive influence on purchase intention. Apart from that, green trust and green attitude are unable to mediate the relationship between green product knowledge and purchase intention.